IMPLEMENTATION OF INQUIRY LEARNING MODEL TO IMPROVE MATHEMATICAL LEARNING OUTCOMES OF STUDENTS IN CLASS VIIIA SMPN 4 TAMBANG - Ratna Syari; Titi Solfitri; Armis (Jurnal Prinsip Pendidikan Matematika, 2020)
This research aims to improve learning process and students’ mathematics learning achievement by applying Inquiry Learning model. Subject of this research are students of VIIIA SMPN 4 Tambang in second semester of academic year 2018/2019 which consist of 29 students. This research is a classroom action research with 2 cycles. The instruments of this research are learning Instrument (Syllabus, Lesson Plans, and Activity Sheets) and data collecting instruments (observation Sheets for teacher and students) and Students’ Mathematic tests. The data collecting techniques in this research are observation techniques and test techniques. The observation sheets were analyzed in qualitative descriptive, while the students mathematic tests were analyzed in quantitative descriptive. Qualitative descriptive analysis results show an improvement of learning process after the implementation of the action (first and second cycle). Quantitative descriptive analysis shows the improvement in students’ mathematic scores. The number of students in the “very high” and “high” interval increases. While the number of students in the “very low”, “low”,and “medium” interval decreases. Based on the result of this research, it can be concluded that the implementation of Inquiry Learning model can be improves the learning process and the students’ mathematics learning achievement in class of VIIIA SMPN 4 Tambang.